Direction of Auditory Pitch-Change Influences Visual Search for Slope From Graphs. (July 2015) - Parrott, Stacey; Guzman-Martinez, Emmanuel; Ortega, Laura; Grabowecky, Marcia; Huntington, Mark D.; Suzuki, Satoru
Linear trend (slope) is important information conveyed by graphs. We investigated how sounds influenced slope detection in a visual search paradigm. Four bar graphs or scatter plots were presented on each trial. Participants looked for a positive-slope or a negative-slope target (in blocked trials), and responded to targets in a go or no-go fashion. For example, in a positive-slope-target block, the target graph displayed a positive slope while other graphs displayed negative slopes (a go trial), or all graphs displayed negative slopes (a no-go trial). When an ascending or descending sound was presented concurrently, ascending sounds slowed detection of negative-slope targets whereas descending sounds slowed detection of positive-slope targets. The sounds had no effect when they immediately preceded the visual search displays, suggesting that the results were due to crossmodal interaction rather than priming. The sounds also had no effect when targets were words describing slopes, such as "positive, " "negative, " "increasing, " or "decreasing, " suggesting that the results were unlikely due to semantic-level interactions. Manipulations of spatiotemporal similarity between sounds and graphs had little effect. These results suggest that ascending and descending sounds influence visual search for slope based on a general association between the direction of auditory pitch-change and visual linear trend.